MOTIVATION AND ADHERENCE IN PHYSICAL AND SPORTING ACTIVITIES IN THE ACADEMIES OF THE CABO FRIO'S CITY / R. J. (Fiep Bulletin - online, 2015)
the sport as social phenomenon of universal characteristics constitutes a true culture form and reflects political and ideological values of the society. Pointed by Tubino (1999) as the largest partner-cultural phenomenon of the end of the century, the sport and the physical activity could prepare the  man for a healthy occupation in the free times. OBJECTIVE: to analyze the decisive initial reasons the participation in a group of four hundred six (406) people in all gymnastics academies in the city of Cabo Frio registered on CREF/RJ and to compare the current factors of adherence. METHODOLOGY: glimpses structured and validated by three Doctors, based on the Likert scale with questions that turned on the reasons alleged for the beginning of the activity and another related to maintenance of the same ones in the academies after a minimum period of three months. MAIN MOTIVATION RESULTS: aesthetics (19,96%), proceeded by the needly of improvement the health (18,12%); and the amount of possible activities offered by the academy (14,68%). The data point in relation to the adherence that the aesthetic patterns continue to be indispensable for the continuity of the activities (19,04%); the maintenance of the health Already obtained (18,42%); Socialization/ coexistence (17,27%). FINAL CONSIDERATIONS: It should be reflected concerning the aesthetic and biological notions, because the fitness phenomenon is an industrialized societies production. There is an increment of the body focus (sexuality, atractivity etc.) and a concern on health. However, the factors of determination find supports in the countless benefits of physical activity told in the literature. Therefore, they should offer activities and opportunities that come to the encounter of the needs and individual motivations. For that it becomes important to know the expectations of that group, in way to stimulate the adoption of new life habits and to contribute for a new perspective of sporting practice and physical activities.
Keywords: physical activities; motivation; academy